STUDENTS’ PERCEPTIONS ON THE USE OF ENGLISH SONGS IN LISTENING CLASSES IN GRADE XI OF SMAN 11 - Nurrahmah Salsabila; Suyadi Suyadi; Nurul Fitri (Universitas Batanghari Jambi, 2026)
This research aims to explore the perceptions of eleventh-grade students at SMAN 11 Jambi City regarding the use of English pop songs, particularly